Making Visible the Invisible: Unionism and Labor Conditions of Domestic Workers in Lima, Peru (Global Journal of Human-Social Science, 2024)
This research paper delves into the pervasive discrimination faced by domestic workers within their work environments, with a specific focus on the context of Lima, Peru. The primary objective is to examine the labour conditions of paid domestic workers and explore the potential role of domestic workers' unions in addressing these issues. Drawing upon a comprehensive review of secondary sources, including surveys, theses, and relevant articles, both quantitative and qualitative data are analysed to understand the complexities of the situation. Conceptual frameworks such as Human Capabilities, Good Living, and Intersectionality are utilized to provide a nuanced understanding of the challenges faced by domestic workers. The paper is structured into four main sections. Firstly, the context of the case is presented through secondary sources, highlighting the prevalence of informality, low wages, and asymmetrical power relations. Secondly, a synthesis of existing literature sheds light on the multifaceted nature of discrimination and labour exploitation within this sector.
Keywords: domestic workers; labour conditions; discrimination; trade union